2018
DOI: 10.1007/s00266-018-1197-8
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Analysis of the External Nose of the Egyptian Males

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
2
14
1
Order By: Relevance
“…In the literature, it is seen that the studies about nose measurement are carried out in methods such as direct measurement, [15][16][17][18][19][20][21][22][23][24] two-dimensional (2D) photogrammetry, 1,4,[25][26][27][28][29][30][31][32][33][34] and three-dimensional (3D) [35][36][37][38] methods. Also, in some studies, more than one method was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, it is seen that the studies about nose measurement are carried out in methods such as direct measurement, [15][16][17][18][19][20][21][22][23][24] two-dimensional (2D) photogrammetry, 1,4,[25][26][27][28][29][30][31][32][33][34] and three-dimensional (3D) [35][36][37][38] methods. Also, in some studies, more than one method was used.…”
Section: Discussionmentioning
confidence: 99%
“…12 Therefore, 2D was used in this study as in most of the publications in the literature. 1,4,[25][26][27][28][29][30][31][32][33][34]39,40 In addition, it is seen in the literature that facial measurements are usually measured with the natural head position 12,41 or Frankfort horizontal plane. 39,42 While the Frankfort horizontal plane is more advantageous in radiological images where bone structures can be seen, the natural head position is more useful in the facial analysis where soft tissue is examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the characteristics of the human nose, the different angles and measurements, and the diversity of the noses among different ethnicities is important for rhinoplasty surgeons during the perioperative planning phase so that the esthetic appearance of the face could be achieved and culturally accepted outcomes could be ensured 3. Although the noses of Middle Eastern individuals can be applied to 4 races (Arabic, Turkish, Persian, and North African), previous studies have described them with a focus on the Persian nose4,5,8–10 Only 1 study measured the anthropometry of Arabian women noses 2. In this study, we compared the angular variables of Arabian women patients undergoing rhinoplasty with previously measured angular variables in the general women population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown significant differences in nasal characteristics and nasolabial area measurements between races and ages. 17,18 These measurements are important in the field of plastic surgery to study facial proportions and aesthetics but are still far from being applicable to the design and clinical application of total nose reconstruction surgery. In the future, total nasal reconstruction will show a personalized development trend, but personalized reconstruction must be based on the parameters of normal noses.…”
Section: Discussionmentioning
confidence: 99%